2016
DOI: 10.1371/journal.pone.0160731
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Vascular Effects after Repeated Intratracheal Instillations of Carbon Black and Lipopolysaccharide

Abstract: Inflammation and oxidative stress are considered the main drivers of vasomotor dysfunction and progression of atherosclerosis after inhalation of particulate matter. In addition, new studies have shown that particle exposure can induce the level of bioactive mediators in serum, driving vascular- and systemic toxicity. We aimed to investigate if pulmonary inflammation would accelerate nanoparticle-induced atherosclerotic plaque progression in Apolipoprotein E knockout (ApoE-/-) mice. ApoE -/- mice were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 67 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, it has been shown that repeated i.t. instillations of lipopolysaccharide, once a week for 10 weeks, increased neutrophilic influx in BALF, without alteration to the extent of atherosclerosis in aorta and BCA (Christophersen et al 2016). Thus, we feel it is unlikely that overt pulmonary inflammation is a pre-requisite for these cardiovascular effects in animal models.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, it has been shown that repeated i.t. instillations of lipopolysaccharide, once a week for 10 weeks, increased neutrophilic influx in BALF, without alteration to the extent of atherosclerosis in aorta and BCA (Christophersen et al 2016). Thus, we feel it is unlikely that overt pulmonary inflammation is a pre-requisite for these cardiovascular effects in animal models.…”
Section: Discussionmentioning
confidence: 89%
“…Inhalation is the golden standard for testing pulmonary toxicity, whereas pulmonary intratracheal instillation allows control of the deposited dose, and is thus suitable for comparison of hazard potential between different particles. We used 0.1% Tween as vehicle [35,59], since all five diesel exhaust particle samples could be dispersed using this vehicle. Furthermore, two different control groups were included, vehicle controls and blank filter extraction controls.…”
Section: Toxicitymentioning
confidence: 99%
“…Nevertheless, we speculate that the altered vasomotor response may be due to bioactive components in plasma that interact with the cellular signaling (e.g., NO production or delivery from endothelial cells to smooth muscle cells) or increases the response to vasoactive drugs. Previously, we have shown that plasma from Printex 90 exposed mice caused vasocontraction in aorta rings from naïve mice [ 31 ]. This type of bioactivity has been described in various studies on pulmonary exposure to particulate matter [ 32 ].…”
Section: Discussionmentioning
confidence: 99%